Southernmost distribution limit for endangered Peladillas (Aplochiton taeniatus) and non-native coho salmon (Oncorhynchus kisutch) coexisting within the Cape Horn biosphere reserve, Chile - Maldonado-Marquez, Alan; Contador Mejias, Tamara Andrea; Rendoll-Carcamo, Javier; Moore, Sabrina; Perez-Troncoso, Carolina; Gomez-Uchida, Daniel; Harrod, Chris (My University, 2020)
The Cape Horn Biosphere Reserve, one of the last wild areas of the planet, is not exempt from the pressures of global change, such as non-native species introductions. During 2018 and 2019 we studied the Robalo river basin in order to update the diversity and distribution of fishes. Here, we report for the first time the native and endangered "Peladillas" Aplochiton taeniatus and the non-native coho salmon Oncorhynchus kisutch. The coexistence of native and non-native fishes poses a challenge for the management and conservation of aquatic biota from the Cape Horn Biosphere Reserve.
Keywords: endangered species; freshwater fish; invasive species; salmonids; sub-antarctic